Interim guidelines for the assessment and treatment of pain in children with multiple sclerosis - Stratton, Catherine; Vassilopoulos, Areti; Brenton, J. Nicholas; Potter, Kirsten; Vargas, Wendy; Rumm, Heather; Bartels, Andrea; Bailey, Mary; Odonkor, Charles; Stoll, Sharon; Zempsky, E. William T.; Yeh, E. Ann; et al. (Frontiers in Neuroscience, 2023)
Introduction Pain in multiple sclerosis (MS) is common, but literature on pain in children with MS remains scarce. Pain has physical, psychological, and social implications in MS, and both comprehensive assessment and interdisciplinary management approaches are needed. We sought to develop an interdisciplinary interim guideline for the assessment and management of pain in children with MS. Methods and materials We convened a modified Delphi panel composed of 13 experts in pediatric and adult MS neurology, physiotherapy, pain, patient lived-experience, advanced practice nursing, psychology, physiatry, and MS research. A survey was sent to panelists for anonymous completion. The panel discussed survey themes extracted by the panel chair. The process was repeated twice. Results Thirteen assessment and treatment recommendations were produced regarding pain in children with MS. Discussion Future studies will assess implementation of these pain assessment and treatment guidelines in the clinical setting.